Understanding Technopreneurship in Agricultural E-Marketplaces - Lestari, Etty Puji; Prajanti, Sucihatiningsih Dian Wisika; Adzim, Fauzul; Primayesa, Elvina; Ismail, Muhammad Iqbal Al-Banna; Lase, Sepandil Laras (Aptisi Transactions On Technopreneurship (ATT), 2024)
Competition in the global market is challenging for technopreneurs to develop strategies that provide a comparative advantage to win the competition. The article aims to develop a model for applying agricultural product e-marketplaces, including the involvement of related stakeholders in Semarang and Magelang Regency, Indonesia. The study employs two primary analytical methods: the MACTOR framework, which assesses alliances, conflicts, and strategic recommendations, and the Analytical Hierarchy Process (AHP) to prioritize decision-making criteria. The results showed that developing agricultural product e-marketplaces requires collaboration from various stakeholders. Notably, consumers, who play a crucial role in the success of the e-marketplace, emerge as the most influential actors, while middlemen are identified as the most dependent. The primary challenge in developing an agricultural product e-marketplace is ensuring smooth food distribution. At the same time, alternative priorities include increasing business partnerships between local agricultural cooperatives and entrepreneurs/investors and providing infrastructure to support the development of e-marketplaces. This study emphasizes the importance of collaboration between various stakeholders in e-marketplace development and implementation of agricultural products so that they can be aligned for the success of the entire e-marketplace system.